Modelling and Regulating Active Harmonic Filters For Improve Power Quality In Transmission Line Environment - P. Senthil; P. Venkatesh Kumar; J. Jayakumar (International Journal of Computational and Experimental Science and Engineering, 2025)
In distributed generation network configuration, power quality is the primary requirement for energy system transmission and distribution. Recent research has shown that in a single-phase system with non-linear loads, the quality of the power control unit needs to be improved for industrial and voltage compensation losses. Previous work has recognized the low harmonics and peak demand in the supplied voltage and current quality and limits the network's reaction to non-linear loads. To solve these power quality issues, active harmonic filters were proposed, and the balance between the source voltage and current components was balanced at the fundamental frequency. In this method, Maximum Power Point Tracking (MPPT) with Artificial Neural Networks (ANN) is used for the solar panels' current and voltage output, which are constantly evaluated, and the controller estimates electrical output. The active filters analyse the input source where the harmonics depend on the voltage regulation and distributed generation depending on the type of sources that create harmonics in the power system. A duty cycle of each switching device acts in an inverter that interfaces to the system through a system interface filter. The simulation output evaluated the peak over shoot, harmonic distortion, and power losses in the transmission Line and improve the output voltage.